Minimal sex-differential modulation of reactivity to pathogens and toll-like receptor ligands following infant Bacillus Calmette–Guérin Russia vaccination - Darboe, F; Adetifa, JU; Reynolds, J; Hossin, S; Plebanski, M; Netea, MG; Rowland-Jones, SL; Sutherland, JS; Flanagan, KL (Frontiers Media, 2017)
Bacillus Calmette–Guérin (BCG), the only licensed vaccine against tuberculosis, has been shown to provide heterologous protection against unrelated pathogens and enhance antibody responses to several routine expanded program on immunization (EPI) vaccines. Understanding these heterologous effects is important for the development of optimal vaccination strategies. We set out to assess the effect of vaccination with BCG Russia of 6-week-old infants on in vitro reactivity to a panel of toll-like receptor (TLR) agonists (TLR2, 4, and 7/8) and heat-killed pathogens [Streptococcus pneumoniae, Candida albicans (CA), and Escherichia coli], and antibody responses to other EPI vaccines compared to BCG naïve infants. We observed no effect of BCG vaccination on innate (TNF-α) or Th2 (IL-4) cytokine responses, but found enhanced CA-specific CD8+IFN-γ+ responses in BCG vaccinated males and females 1 week after vaccination and decreased IFN-γ:IL4 ratio to SP in females. By 12 weeks (but not 1 week) of post-vaccination, there was significant downmodulation of Th1 cytokine responses in BCG vaccinated infants; and TLR-stimulated IL-10 and IL-17 responses declined in BCG vaccinated females but not males. Significant changes also occurred in the BCG naïve group, mainly at 18 weeks, including decreased Th1 and increased IL-10 responses. The effects at 18 weeks were most likely a result of immune modulation by the intervening EPI vaccines given at 8, 12, and 16 weeks of age. There was no effect of BCG vaccination on EPI antibody levels at either time point. Taken together, our results support minimal early heterologous immune modulation by BCG Russia vaccination that did not persist 12 weeks after vaccination.